Evaluating Merdeka Curriculum Policy in Indonesia Based on the William Dunn Model - Sarrayu, Anggraeni Eka; Budi Purwoko, Mufarrihul Hazin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study evaluates the implementation of Indonesia's Merdeka Curriculum, a pivotal shift in national education policy promoting student-centered learning, through William Dunn's policy evaluation model. Employing a mixed-methods approach, the research integrates qualitative data from in-depth interviews with educational stakeholders—including policymakers, administrators, teachers, students, and parents—to capture rich, contextualized insights on their experiences, perceptions, and challenges. Quantitative data on student achievement, teacher performance, and school resources are analyzed to measure tangible outcomes. The findings reveal a moderate level of curriculum understanding among teachers, who express the need for more comprehensive training and resources. Key challenges identified include inadequate infrastructure, complexities in learning evaluation, disparities in student and family conditions, and inconsistencies in government policies. Addressing these issues is crucial for successful implementation and maximizing the curriculum’s potential to transform Indonesian education. The study underscores the importance of targeted interventions and support mechanisms to ensure the Merdeka Curriculum achieves its goals of improving educational quality and relevance for 21st-century learners, fostering independence, innovation, and adaptability.